2014
DOI: 10.3389/fpsyg.2014.00207
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between the anticipation and subsequent online processing of emotional stimuli as measured by pupillary dilatation: the role of cognitive reappraisal

Abstract: Emotions can occur during an emotion-eliciting event, but they can also arise when anticipating the event. We used pupillary responses, as a measure of effortful cognitive processing, to test whether the anticipation of an emotional stimulus (positive and negative) influences the subsequent online processing of that emotional stimulus. Moreover, we tested whether individual differences in the habitual use of emotion regulation strategies are associated with pupillary responses during the anticipation and/or on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Regarding emotion regulation, it might be reasonable to assume that pupil dilation reflects autonomic activation associated with both emotion regulation effort and emotion regulation success. In line with this notion, recent data revealed that larger pupillary responses during the anticipation of emotional stimuli predicted smaller pupil sizes during actual emotion processing (Vanderhasselt, Remue, Ng, & De Raedt, ). Interestingly, this temporal interplay was particularly observed in individuals habitually using reappraisal to regulate their emotions.…”
mentioning
confidence: 60%
“…Regarding emotion regulation, it might be reasonable to assume that pupil dilation reflects autonomic activation associated with both emotion regulation effort and emotion regulation success. In line with this notion, recent data revealed that larger pupillary responses during the anticipation of emotional stimuli predicted smaller pupil sizes during actual emotion processing (Vanderhasselt, Remue, Ng, & De Raedt, ). Interestingly, this temporal interplay was particularly observed in individuals habitually using reappraisal to regulate their emotions.…”
mentioning
confidence: 60%
“…However, for about 120 years, pupil sizes have been found to be additionally and systematically influenced by cognitive processing [3, 4]. For instance, pupil size changes have been studied in decision-making [58], attention [4, 922], emotions [23, 24], language [25], and memory [2629]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that cognitive effort exerted during anticipation of an emotion eliciting stimulus is related to lower cognitive effort when confronted with that stimulus (Vanderhasselt, Remue, Ng, & De Raedt, 2014). In this latter study, participants' pupillary responses (as a proxy of cognitive effort, related to DLPFC) were recorded while they were naturally responding to emotional stimuli.…”
Section: Anticipation and Proactive Controlmentioning
confidence: 99%